Analisis Perilaku Konsumen pada Mini Market 212 Martujung Harapan Bekasi - Elva Muntazia; Diana Prihandini (JAMBIS : Jurnal Administrasi Bisnis, 2021)
The awakening spirit of the people during 212 rally had formeda forum to advance the economy of Muslim people :212 Sharia Cooperative,and had initiated the birth of 212 Mart, an Islamic mini market with the concept of sharing economy. The concept was different from the concept the previously existing mini markets. The implementation of sharing economy concept was highly appropriate and suitable with the basic principle soft rade according to Islam. Based on the result of the study analyzed,the customers especially Muslims responded and welcomed the presence of 212 Mart well. The factors that affected the customers indeciding to buy at 212 Mart were cultural, social, production/personal, and factor psychological factors.However, the factors that kept the customers from buying at 212 Mart included the ongoing Covid-19 pandemic,incomplete products, higher price forsome products, andnot quiterecognized bythesociety. Theresearch methodused was descriptive qualitative. The data collection techniques used were observation,interview,and documentation.